2015
DOI: 10.1159/000437016
|View full text |Cite
|
Sign up to set email alerts
|

Waist Circumference as a Predictor of Failure of Sonographic Estimation of Fetal Birth Weight

Abstract: Objective: Several factors may interfere with the success of fetal birth weight (BW) prediction. In this study we tried to determine the most probable factors that may lead to unsuccessful BW estimation. Methods: 200 consecutive pregnancies between 34 and 41 weeks of gestation were enrolled for the study. All subjects underwent sonographic fetal BW estimation before membrane rupture or engagement of presented part. Sonography was performed by the same sonographer blinded to the study design. Failure of estimat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
(22 reference statements)
0
1
0
Order By: Relevance
“…Maternal waist circumference could be an indicator of higher abdominal wall thickness and fat. Recently, it was reported that maternal waist circumference could be predictive of fetal weight estimation failure, and 105 cm was defined as an optimal cut‐off value with 70% sensitivity and 61% specificity . Nonetheless, it is concluded here that fetal biometric measurements were highly reproducible in both patients with higher and lower maternal abdominal waist circumferences.…”
Section: Discussionmentioning
confidence: 69%
“…Maternal waist circumference could be an indicator of higher abdominal wall thickness and fat. Recently, it was reported that maternal waist circumference could be predictive of fetal weight estimation failure, and 105 cm was defined as an optimal cut‐off value with 70% sensitivity and 61% specificity . Nonetheless, it is concluded here that fetal biometric measurements were highly reproducible in both patients with higher and lower maternal abdominal waist circumferences.…”
Section: Discussionmentioning
confidence: 69%